SECURITY OF ARTIFICIAL INTELLIGENCE IN SELF-DRIVING CARS - Ganzha Dmitry (2018)
SECURITY OF ARTIFICIAL INTELLIGENCE IN SELF-DRIVING CARS Summary This thesis has the aim to research and find out whether artificial intelligence is secure to use in autonomous cars. The work will focus on the development of artificial intelli-gence, the different levels of automation. The major hurdles of implementing artificial intelligence and its systems in self-driving cars will be analysed and described. Since ar-tificial intelligence is a complex topic a definition of artificial intelligence is necessary to get a proper understanding of the matter. As with autonomous driving not only the technical aspect plays a role it will be useful to cover all other aspects involved by re-searching challenges associated with ethics and regulatory issues. Thereby the history of artificial intelligence will be briefly described and a detailed overview of autonomous levels will be done. Moreover current trends and the current state of artificial intelli-gence in autonomous cars will be presented and discussed. Additionally the core focus of this work will be laid on the security and cybersecurity of artificial intelligence in auton-omous cars. Security threats and possible dangers in autonomous cars with artificial in-telligence will be identified and explained. Furthermore recommendations and possible solutions will be presented. This will represent the research gap. Consequently this thesis will try to provide new findings and knowledge by conducting a thorough literature re-view for this topic. Furthermore qualitative data in form of expert interviews in the qual-itative research part will be done. The experts are carefully selected from the respective field of research which is artificial intelligence and automotive industry. This will then lead to a conclusion which is based on the conducted research and the expert interviews. The study shows that there are still many unresolved issues with artificial intelligence in self-driving cars. Regarding the security issues there are also improvements possible which should help to accelerate the move to highly autonomous vehicles.